14.3.4 problem 6

Internal problem ID [2513]
Book : Differential equations and their applications, 4th ed., M. Braun
Section : Chapter 1. First order differential equations. Section 1.9. Exact equations. Excercises page 66
Problem number : 6
Date solved : Monday, January 27, 2025 at 05:56:51 AM
CAS classification : [[_1st_order, _with_linear_symmetries], [_Abel, `2nd type`, `class A`]]

\begin{align*} \frac {y^{2}}{2}-2 \,{\mathrm e}^{t} y+\left (-{\mathrm e}^{t}+y\right ) y^{\prime }&=0 \end{align*}

Solution by Maple

Time used: 1.043 (sec). Leaf size: 45

dsolve((y(t)^2/2-2*y(t)*exp(t))+(y(t)-exp(t))*diff(y(t),t)=0,y(t), singsol=all)
 
\begin{align*} y &= \left (1-\sqrt {\left ({\mathrm e}^{3 t}+c_1 \right ) {\mathrm e}^{-3 t}}\right ) {\mathrm e}^{t} \\ y &= \left (1+\sqrt {\left ({\mathrm e}^{3 t}+c_1 \right ) {\mathrm e}^{-3 t}}\right ) {\mathrm e}^{t} \\ \end{align*}

Solution by Mathematica

Time used: 1.342 (sec). Leaf size: 70

DSolve[(y[t]^2/2-2*y[t]*Exp[t])+(y[t]-Exp[t])*D[y[t],t]==0,y[t],t,IncludeSingularSolutions -> True]
 
\begin{align*} y(t)\to e^t-\frac {\sqrt {-e^{3 t}-c_1}}{\sqrt {-e^t}} \\ y(t)\to e^t+\frac {\sqrt {-e^{3 t}-c_1}}{\sqrt {-e^t}} \\ \end{align*}